As dinâmicas praxeológicas e cognitivas e a construção do conhecimento didático do professor de matemática - MESQUITA, Flávio Nazareno Araujo (Universidade Federal do Pará, 2012)
This work is an autobiographical narrative research that seeks to understand how the mathematical praxeology, experienced by me, as a math teacher and a student of continuing education courses, can contribute, prevent, or even be neutral in the building of a new didactic praxeology about solving equations of second degree in elementary education. Under lightof anthropological theory didactic, more precisely of its cognitive dimension, are explored notions of dynamic and praxeological a person to analyze the two phases of internal didactic transposition, performed in a class of fourth stage of the EJA. The results indicate that the equipment and the cognitive universe praxeological for the mathematical object in question contribute to buildingnew praxeology mathematics. But the way of thinking and doing occasional classroom teachers can determine the actions and do not allow the connections between mathematical objects intended in the first phase of the didactic transposition of the internal object of study. There is, therefore, to break this cultural spot to allow teachers and renew equipment and cognitive praxeological teacher.